Antioxidant and Inhibition Lipase Enzyme Activity of Centella asiatica Leaf Extract - Yunarto, Nanang; Mawadatun, Ummi; Reswandaru, Uud Nourma; Sopian, Ahmad; Isnawati, Ani; Alegantina, Sukmayati (Jurnal Kefarmasian Indonesia, 2023)
Hyperlipidemia and many other metabolic diseases are related to oxidative stress. Centella asiatica is a herbal medicine with reported antioxidant effect in vitro. Centella asiatica contains secondary metabolites asiaticoside which are included in the terpenoid group. The study evaluated the respective antioxidant potential and lipase enzyme inhibition of Centella asiatica leaves extract (CAE). Centella asiatica were extracted in ethanol, and the extract was assayed for the measurement of asiaticoside. Ethanolic extracts of asiaticoside content were prepared for HPLC analysis The antioxidant potential of extracts was assessed by its free radical scavenging activity such as 2, 2-diphenyl -1-picrylhydrazyl as well as reducing. The anti-hyperlipidemic effect was evaluated in vitro lipase inhibitory activity test carried out enzymatically using the ELISA method with simvastatin as a comparison. The results showed asiaticoside contain in CAE 1.26%; the IC50 value of the antioxidant test of CAE was 11.38 g/mL; the IC50 value of the lipase enzyme in the CAE was 26.14 g/mL. The antioxidant activity of CAE is categorized as very strong and has the potential to inhibit lipase enzymes. The study suggests that CAE has the potential to inhibit lipase activity, suppressing lipid digestion and thereby diminishing entry of lipids into the body.